Pemberdayaan Ibu Rumah Tangga Di Desa Danau Ganting Kecamatan Dusun Selatan Kabupaten Barito Selatan - laili wahyunita; Muhammad Aldi Prayudha; Moh Imam; Achmad Nur Ravi; Wahinul Asmi (CV. Ulil Albab Corp, 2022)
Fish is the biggest asset in Danau Ganting Village, Dusun Selatan District, South Barito Regency. Since Lake Ganting Village was formed, the majority of villagers work as fishermen due to the abundance of fish resources in Danau Ganting Village. This is evidenced through an interview with the Department of Food Security, Agriculture and Fisheries Unit 1 which stated that in the past two years, more precisely in 2018-2020, South Barito was one of the contributors to the largest fish catch in Central Kalimantan for two consecutive years. However, usually the villagers through the catch of fish they can usually sell directly to agents who come to the village or sell it to the market directly. In fact, the fish caught can be processed into high-value food and become an alternative to improve the economy and public health in general. Thus, through a program of processing fish into varied and productive food, skills can be improved so that it becomes an economic and productive innovation for the community itself and for the village.